Pelatihan Pembuatan Cookies dan Mie Kering Tempe Koro Pedang dan Penyuluhan Label Pangan di Pulutan - Brigitta Laksmi Paramita; Benediktus Yudo Leksono; Venansius Galih Perkasa Putra (Seminar Nasional Penelitian dan Abdimas, 2024)
Kampung Mengger has been known as the area with a high number of jack bean production. Jack bean tempeh has been developed to enhance the functional benefits. However, the innovation and quality enhancement of jack bean tempeh-based products are still needed by means of products training and knowledge sharing about food labels. Jack bean tempeh-based products which are going to be delivered are dried noodles and cookies. This activity aims to deliver the knowledge and skill to society regarding jack bean tempeh-based products, dried noodles and cookies as well as food labels. This activity was carried out for series such as products training (dried noodles and cookies), knowledge sharing about food labels, food nutrition composition analysis, and food label design which has been attended by 15 participants. Participants directly committed the process of dried noodles and cookies making and food label design was used in product’s packaging. By means of this activity, participants obtained the knowledge and skill for jack bean tempeh-based products (dried noodles and cookies) as well as food labels for enterprise and product quality improvement.